2018
DOI: 10.1186/s13638-018-1247-6
|View full text |Cite
|
Sign up to set email alerts
|

A novel torque sensor based on the angle of magnetization vector

Abstract: Torque is an important parameter of a mechanical power system, which reflects transmission efficiency, transmission reliability, and operating conditions of equipment. Torque monitoring is very important for real-time control and fault diagnosis of mechanical equipment. A torque measurement method based on the theory of magnetic effect is proposed for multipoint torque monitoring in shafting. A model of the deflection angle of the magnetization vector and torque is established based on the theory of magnetic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…This work offered a viable technique to support condition-based maintenance and early fault detection systems by tracking component vibrations. Later, Huang et al [349] reported an online torque monitoring approach relying on advanced ML models to harvest magnetization vector deflection angle and different torsional loads. The authors recorded a maximum torque sensitivity of 17.7 mV/Nm and a nonlinearity error of 0.77% FS in a range from 9.71 Nm to 93.35 Nm.…”
Section: ) Force and Torque Sensorsmentioning
confidence: 99%
“…This work offered a viable technique to support condition-based maintenance and early fault detection systems by tracking component vibrations. Later, Huang et al [349] reported an online torque monitoring approach relying on advanced ML models to harvest magnetization vector deflection angle and different torsional loads. The authors recorded a maximum torque sensitivity of 17.7 mV/Nm and a nonlinearity error of 0.77% FS in a range from 9.71 Nm to 93.35 Nm.…”
Section: ) Force and Torque Sensorsmentioning
confidence: 99%
“…Despite its simple installation process, this method exhibits limitations in measurement precision, susceptibility to external interferences, and relatively slow response speed. Apart from this method, in [ 12 ], the relationship between the deflection angle of the magnetization vector and torque is established based on the principle of electromagnetic effects and a non-contact torque measurement system utilizing Hall sensors is proposed. In [ 13 ], a torque measurement device based on the Hall effect is also introduced.…”
Section: Introductionmentioning
confidence: 99%